Variation Analysis of Genetic Variants of Teak Arboretum with Microsatellite Markers - Imas Cintamulya (Pascasarjana Universitas Negeri Malang (UM), 2013)
Analisis Variasi Genetik Varian Jati Arboretum dengan Penanda Mikrosatelit Abstract: The selection of teak is to obtain superior properties is not enoughby only through morphological markers , but also need to use molecular markers based on DNA polymorphism. Based on these studies, it is need to be done in terms of plant genetic identity at the DNA level, to look at genetic variation. Genetic variation identity information required for the supply of seeds for the development of industrial tree plantations, with the aim of preventing inbreeding and for conservation purposes. The purpose of this study is to analyze the genetic variations teak variant arboretum with microsatellite molecular markers and develop enrichment book studies of the molecular basics of plant particularly microsatellite molecular markers in the analysis of genetic variation in resulting of high quality variants of teak-arboretum. As for achieving the first objective research steps performed is as follows: DNA isolation, DNA amplification, and electrophoresis of amplification product. The data obtained are analyzed with the GENEPOP Package version 4.0.10 program, the results are in the form of information about the frequency of alleles, heterozygosity, genic and genotype differentiation, and migration of alleles. The research design is by Plomp (1997) which only up to 4 stages, namely: 1) the initial assessment stage; 2) design stage; 3) the realization phase (construction); and 4) the stage of testing, evaluation, and revision. The conclusions obtained are: 1) variant of teak arboretum showed as high genetic variation; 2) resulted in the enrichment of book studies the molecular basics of plant quality. Key Words: genetic variation, variant teak, arboretum, microsatellite markers, books enrichment Abstrak: Seleksi tanaman jati untuk memperoleh sifat unggul tidak cukup melalui penanda morfologi, tetapi juga perlu digunakan penanda molekuler berdasarkan polimorfisme DNA. Berdasarkan hal tersebut perlu dilakukan kajian tanaman jati dari segi genetik pada level DNA, untuk melihat variasi ge-netik. Informasi variasi genetik jati diperlukan dalam pengadaan bibit untuk pembangunan hutan tanaman industri, dengan tujuan mencegah terjadinya inbreeding dan untuk keperluan konservasi. Tujuan penelitian ini adalah untuk menganalisis variasi genetik varian jati arboretum dengan penanda molekuler mikrosatelit dan menyusun buku pengayaan kajian dasar-dasar molekuler tumbuhan khusus-nya penanda molekuler mikrosatelit dalam menganalisis variasi genetik varian jati arboretum yang berkualitas. Adapun untuk mencapai tujuan pertama dilakukan langkah-langkah penelitian sebagai berikut: isolasi DNA, amplifikasi DNA, dan elektroforesis hasil amplifikasi. Data yang sudah diperoleh dianalisis dengan program GENEPOP Package versi 4.0.10, hasilnya berupa informasi mengenai frekuensi alel, heterozigositas, genic dan genotype differentiation, serta migrasi alel. Rancangan peneliti-an yang digunakan menurut Plomp (1997) yang hanya sampai 4 tahap, yakni: 1) tahap pengkajian awal; 2) tahap perancangan; 3) tahap realisasi (konstruksi); dan 4) tahap pengujian, evaluasi, dan revisi. Simpulan yang didapat adalah: 1) varian jati arboretum menunjukkan adanya variasi genetik yang tinggi; 2) menghasilkan buku pengayaan kajian dasar-dasar molekuler tumbuhan yang berkualitas.Kata kunci: variasi genetik, varian jati, arboretum, penanda mikrosatelit, buku pengayaan